Beyond Tweets: Mass and Group Convergence Communication in Yogyakarta Fandom - Nourmalihah Tsaqif Kusindriyanti; Prahastiwi Utari; Sudarmo (International Journal of Media and Communication Research, 2025)
Social media has revolutionized communication, creating new spaces for interaction and expression. This study examines the Stray Kids Yogyakarta community on Twitter (@straykids_YK), a fanbase for the South Korean idol group Stray Kids, established in December 2017. Although interaction on Twitter is limited, community organizers try to increase engagement by providing information about upcoming events and joint projects with other fanbase accounts, hoping to increase community awareness. This research, based on qualitative and case study methods, explores the role of the Stray Kids Yogyakarta community through interviews with administrators and community members. The study revealed that the Stray Kids Yogyakarta community thrives through active communication on WhatsApp, Instagram, and in-person meetings, despite limited Twitter engagement. Interviews highlighted that while Twitter needs improvement, the community is vibrant and well-connected, showing strong adaptability and dedication among fans. This indicates the community's ability to maintain robust connections and engagement across multiple platforms.